Mekanisme Pengajuan Klaim, Persyaratan dan Cara Pencairan Dana Jaminan Hari Tua pada BPJS Ketenagakerjaan - Sukriawan Sukriawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One of the agencies formed by the government in handling social security is PT Jamsostek which has now changed to BPJS Ketenagakerjaan. BPJS Ketenagakerjaan consists of Old Age Security (JHT), Death Security (JK), Work Accident Security (JKK), and Pension Security (JP). In submitting a BPJS Ketenagakerjaan claim itself, you can go through the official SSO website (E-claim), the BPJSTKU Mobile application, the Antrian.bpjsketenagakerjaan.go.id site, and you can come in person. In principle, the method for claiming BPJS Ketenagakerjaan Old Age Security via E-claim or via the BPJSTKU Mobile application is not much different. After completing the requirements and documents, applicants only need to wait for the data verification schedule to the nearest BPJSTK office. And the method for disbursing BPJS Ketenagakerjaan Old Age Security can also be done offline or online. The purpose of this study was to determine the mechanism for submitting claims to BPJS Ketenagakerjaan Old Age Security with the ease of accessing claims, namely by using the E-claim feature and the requirements that must be submitted by BPJS Ketenagakerjaan participants in submitting claims and how to disburse BPJS Ketenagakerjaan Old Age Security funds in a structured manner. The results of this study are that there is convenience provided by BPJS Ketenagakerjaan Old Age Security in serving the claim system for participants by providing an E-claim system and the mechanism is quite easy to understand and access.